2014
DOI: 10.1371/journal.pone.0112349
|View full text |Cite
|
Sign up to set email alerts
|

Australian Gay and Bisexual Men’s Attitudes to HIV Treatment as Prevention in Repeated, National Surveys, 2011-2013

Abstract: ObjectiveAssess the acceptability of HIV treatment as prevention and early antiretroviral treatment among gay and bisexual men in Australia and any changes in attitudes over time.MethodsNational, online, cross-sectional surveys of gay and bisexual men were repeated in 2011 and 2013. Changes in attitudes to HIV treatment over time were assessed with multivariate analysis of variance. The characteristics of men who agreed that HIV treatment prevented transmission and thought that early treatment was necessary we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 20 publications
5
22
1
Order By: Relevance
“…For example,Holt et al (2016) report that HIV positive MSM in Australia are increasingly more likely to believe that ART can prevent HIV transmission and that men who endorsed beliefs that HIV treatments prevent HIV are significantly more likely to engage in condomless anal sex. Similar changes are observed in MSM who are HIV uninfected, with beliefs that ART prevents HIV coincide with increases in condomless anal sex over time (Holt et al, 2014; Holt et al, 2016). Increased beliefs related to the potential for ART to prevent HIV transmission are associated with reductions in condom use in several countries (Laga & Piot, 2012), including Brazil (Hanif et al, 2014) and the United States (Kalichman, Eaton, & Cherry, 2010).…”
Section: Introductionmentioning
confidence: 53%
“…For example,Holt et al (2016) report that HIV positive MSM in Australia are increasingly more likely to believe that ART can prevent HIV transmission and that men who endorsed beliefs that HIV treatments prevent HIV are significantly more likely to engage in condomless anal sex. Similar changes are observed in MSM who are HIV uninfected, with beliefs that ART prevents HIV coincide with increases in condomless anal sex over time (Holt et al, 2014; Holt et al, 2016). Increased beliefs related to the potential for ART to prevent HIV transmission are associated with reductions in condom use in several countries (Laga & Piot, 2012), including Brazil (Hanif et al, 2014) and the United States (Kalichman, Eaton, & Cherry, 2010).…”
Section: Introductionmentioning
confidence: 53%
“…21 A more recent survey, conducted in 2013, found that both groups continued to believe in the health benefits of ART, but had diverging views about treatment as prevention (negative men continuing to be more sceptical about these potential benefits of ART), and early initiation (positive men being far less supportive of commencing treatment soon after diagnosis). 22 Promoting the health, rather than preventive, benefits of ART continues to be most acceptable to both HIV positive and negative gay men in Australia.…”
mentioning
confidence: 99%
“…This suggests a growing awareness of "treatment as prevention" among Australian men who have sex without condoms, despite community skepticism about the concept. 24 In contrast, the use of antiretroviral medication by HIV-negative and untested men remains relatively uncommon, 18 perhaps reflecting the lack of formal availability of PrEP in 2013 in Australia.…”
Section: Discussionmentioning
confidence: 99%